2013
DOI: 10.1021/cm402729r
|View full text |Cite
|
Sign up to set email alerts
|

Incommensurate Modulation and Luminescence in the CaGd2(1–x)Eu2x(MoO4)4(1–y)(WO4)4y (0 ≤ x ≤ 1, 0 ≤ y ≤ 1) Red Phosphors

Abstract: Scheelite related compounds (A′,A″) n [(B′,B″)O4] m with B′, B″ = W and/or Mo are promising new light-emitting materials for photonic applications, including phosphor converted LEDs (light-emitting diodes). In this paper, the creation and ordering of A-cation vacancies and the effect of cation substitutions in the scheelite-type framework are investigated as a factor for controlling the scheelite-type structure and luminescent properties. CaGd2(1–x)Eu2x (MoO4)4(1–y)(WO4)4y (0 ≤ x ≤ 1, 0 ≤ y ≤ 1) solid soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 51 publications
1
50
0
Order By: Relevance
“…This result accompanies the incommensurately modulated structure induced by the anion deficient MoO 4 À x group. This incommensurately modulated structures in the scheelite-type tetragonal phase were also observed in various molybdates and tungstates as a cation deficient structure [32][33][34]. Previously, our research group has reported the incommensurately modulated structure of CaGd 2 (WO 4 ) 4 :Er 3 þ /Yb 3 þ phosphors induced by the difference of effective ionic radii of Yb 3 þ , Er 3 þ and Gd 3 þ 4 Er 0.05 Yb 0.45 is higher than that of (c) PbLa 1.7 (MoO 4 ) 4 :Er 0.1 Yb 0.2 .…”
Section: Methodssupporting
confidence: 63%
“…This result accompanies the incommensurately modulated structure induced by the anion deficient MoO 4 À x group. This incommensurately modulated structures in the scheelite-type tetragonal phase were also observed in various molybdates and tungstates as a cation deficient structure [32][33][34]. Previously, our research group has reported the incommensurately modulated structure of CaGd 2 (WO 4 ) 4 :Er 3 þ /Yb 3 þ phosphors induced by the difference of effective ionic radii of Yb 3 þ , Er 3 þ and Gd 3 þ 4 Er 0.05 Yb 0.45 is higher than that of (c) PbLa 1.7 (MoO 4 ) 4 :Er 0.1 Yb 0.2 .…”
Section: Methodssupporting
confidence: 63%
“…1). These reflections are attributed to cation-vacancy ordering and the formation of modulated structures [20,22,26,[28][29][30]. …”
Section: Preliminary Characterizationmentioning
confidence: 99%
“…Typically, occupational modulations in scheelite-based structures are confined to the ab planes, so that the ED taken along the [001] zone axis are the most informative [20,22,26,[28][29][30]. …”
Section: Tem Studymentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 As we know, the structural disorder is a positive factor for the creation of wideemission-band phosphors in the doped systems. [15][16][17] More recently, the evaluation of the ''1147'' systems was continued and now the general formula can be written as LnBaM 4 O 7 (Ln = rare earth and Ca; M = Co, Fe, Mn, Zn, Ga, and Al). [18][19][20] Several rare-earth-containing phosphors were proposed from the LnBaM 4 O 7 -type hosts when M = Zn or Ga. [21][22][23] Up to now, however, self-activated luminescence remained unknown in this kind of complex oxide system.…”
Section: Introductionmentioning
confidence: 99%